Leaves of Cedrela sinensis Attenuate Chronic Unpredictable Mild Stress-Induced Depression-like Behavior via Regulation of Hormonal and Inflammatory Imbalance - Hye Rin Jeong; Jong Min Kim; Uk Lee; Jin Yong Kang; Seon Kyeong Park; Hyo Lim Lee; Jong Hyun Moon; Min Ji Kim; Min Ji Go; Ho Jin Heo (MDPI AG, 2022)
This study aimed to evaluate the protective effects of ethyl acetate fraction from Cedrela sinensis (EFCS) against chronic unpredictable mild stress (CUMS)-induced behavioral dysfunction and stress response in C57BL/6 mice. The physiological compounds of EFCS were identified as rutin, isoquercitrin, ethyl gallate, quercitrin, kaempferol-3-O-rhamnoside, and ethyl digallate, using UPLC-Q-TOF/MSE. To evaluate the neuroprotective effect of EFCS, H2O2− and corticosterone-induced neuronal cell viability was conducted in human neuroblastoma MC-IXC cells. It was found that EFCS alleviated depression-like behavior by conducting the sucrose preference test (SPT), forced swimming test (FST), open field test (OFT), and tail suspension test (TST). EFCS inhibited mitochondrial dysfunction related to neuronal energy metabolism by regulating reactive oxygen species (ROS) levels, mitochondrial membrane potential (MMP), and ATP contents in brain tissue. In addition, the administration of EFCS regulated the stress hormones in serum. EFCS regulated stress-related indicators such as CRF, ACTH, CYP11B1, and BDNF. Moreover, EFCS downregulated the inflammatory responses and apoptosis proteins such as caspase-1, TNF-α, IL-1β, p-JNK, BAX, and p-tau in brain tissues. These results suggest that EFCS might be a potential natural plant material that alleviates CUMS-induced behavior disorder by regulating inflammation in brain tissue against CUMS-induced depression.